Effect of gamma irradiation on seedling parameters of amaranthus (Amaranthus cruentus) genotype IC-35539 - Amar Singh Yadav; Prashant Kumar Rai; Vaidurya Pratap Sahi; Neha Thomas (Annals of Agricultural Research, 2024)
The present study was conducted to evaluate the effect of different doses of gamma irradiation on seedling parameters and nutritional values of Amaranthus genotype IC-35539 in the Notified State Seed Testing Laboratory of the Department of Genetics and Plant Breeding, Sam Higginbottom University of Agriculture, Technology, and Sciences, Prayagraj (Uttar Pradesh), during July, 2023 to June, 2024 in complete randomized design with four replications. The seeds of amaranthus genotype were treated with 10 treatments of gamma doses ranging from 5 kR to 50 kR (T1 to T10) alongwith control (T0). Observations included seed germination percentage, germination energy, shoot and root length, seedling length, fresh and dry weight of seedlings, seed vigour indices I and II and nutritional components such as protein, carbohydrate, ash, moisture, iron, zinc, calcium, and magnesium. Results indicated that lower doses of gamma irradiation, particularly at 5 kR, significantly enhanced seedling parameters such as germination percentage, germination energy, shoot and root length, seedling length, fresh and dry weight, and vigour indices. The 10 kR dose also showed positive effects, albeit to a lesser extent. Conversely, higher doses, especially 50 kR, adversely affected seedling growth, demonstrating a dose-dependent response were increased gamma irradiation diminished seedling performance. The 5 kR treatment not only improved seedling parameters but also positively influenced the nutritional and mineral composition of the plants. In conclusion, the 5 kR dose emerged as the most effective treatment for enhancing both growth and nutritional quality in Amaranthus genotype IC-35539. These findings suggest that optimizing gamma irradiation doses can be a valuable strategy for improving plant breeding and cultivation practices.